2022
DOI: 10.1002/jcb.30274
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the lysosome: Mechanisms and treatments for nonalcoholic fatty liver disease

Abstract: The multiple functions of the lysosome, including degradation, nutrient sensing, signaling, and gene regulation, enable the lysosome to regulate lipid metabolism at different levels. In this review, I summarize the recent studies on lysosomal regulation of lipid metabolism and the alterations of the lysosome functions in the livers affected by nonalcoholic fatty liver disease (NAFLD). NAFLD is a highly prevalent lipid metabolic disorder. The progression of NAFLD leads to nonalcoholic steatohepatitis (NASH) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Studies have shown that lysosomes are closely related to the processes of lipid metabolism. [52][53][54] Therefore, we examined the quantity and function of lysosomes in hepatocytes to investigate whether the ameliorative effect of Ace Pg3G on lipid deposition was related to lysosomes. Also, given that Pg3G did not display a positive effect on oxidative stress or lipid deposition, subsequent experiments to explore the mechanism will focus on Ace Pg3G.…”
Section: Ace Pg3g Increased Lysosomal Quantity and Enhanced Lysosomal...mentioning
confidence: 99%
“…Studies have shown that lysosomes are closely related to the processes of lipid metabolism. [52][53][54] Therefore, we examined the quantity and function of lysosomes in hepatocytes to investigate whether the ameliorative effect of Ace Pg3G on lipid deposition was related to lysosomes. Also, given that Pg3G did not display a positive effect on oxidative stress or lipid deposition, subsequent experiments to explore the mechanism will focus on Ace Pg3G.…”
Section: Ace Pg3g Increased Lysosomal Quantity and Enhanced Lysosomal...mentioning
confidence: 99%
“… 72 Therefore, reactivation of ALP via regulation of the mTORC1–TFEB axis has great therapeutic potential in MAFLD treatment. 124 …”
Section: The Effects and Functional Targets Of Natural Products In Th...mentioning
confidence: 99%
“…Interestingly, the strategy of targeting the lysosome has seemed to encourage a new direction for future NAFLD treatment, e.g. , inhibition of mTOR localized on the lysosome surface and restoration of normal lysosomal function and autophagy[ 75 ]. Nevertheless, all of the studies are limited to animal models.…”
Section: Challenges In Treatmentmentioning
confidence: 99%